2007
DOI: 10.1002/jbm.a.31248
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of the superficial layer of articular cartilage

Abstract: To gain more information on the mechanism of lubrication in articular joints, the superficial layer of bovine articular cartilage was mechanically removed in a sheet of ice that formed on freezing the cartilage. Freeze-dried samples contained low concentrations of chondroitin sulphate and protein. Analysis of the protein by SDS PAGE showed that the composition of the sample was comparable to that of synovial fluid (SF). Attenuated total reflection infrared (ATR-IR) spectroscopy of the dried residue indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…On closer inspection, the biochemical changes in cartilage after PAO were greater in the superficial than in the deeper cartilage zone, suggesting a higher response of the superficial zone compared with the deeper zone to changes in biomechanics or the possible nonbiomechical factors including the inflammatory process in the joint after surgery. This confirms the findings of several other authors, indicating depth-related properties and metabolic specialization of the resident chondrocytes leading to characteristic zonal variations in cartilage adaption to mechanical loading [9,36,43]. In addition, the unique depth-dependent features and high vulnerability of the superficial layer have been demonstrated in a study investigating the effect of inflammatory cytokines in different cartilage layers [13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On closer inspection, the biochemical changes in cartilage after PAO were greater in the superficial than in the deeper cartilage zone, suggesting a higher response of the superficial zone compared with the deeper zone to changes in biomechanics or the possible nonbiomechical factors including the inflammatory process in the joint after surgery. This confirms the findings of several other authors, indicating depth-related properties and metabolic specialization of the resident chondrocytes leading to characteristic zonal variations in cartilage adaption to mechanical loading [9,36,43]. In addition, the unique depth-dependent features and high vulnerability of the superficial layer have been demonstrated in a study investigating the effect of inflammatory cytokines in different cartilage layers [13].…”
Section: Discussionsupporting
confidence: 91%
“…However, no synovial fluid layer could be detected on a single morphological True-FISP reformat, most likely as a result of the extreme thinness of this layer. Furthermore, it has been reported that the protein composition of the superficial layer is almost indistinguishable from that of synovial fluid [9]; therefore, we considered that our approach is reasonable for evaluating the superficial zone. Second, the lack of a control group (natural history group) is a limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our laboratories, the superficial layer was removed mechanically from the articular surface of natural bovine cartilage and analysed for phospholipid, protein, glycosaminoglycan and hyaluronan [29]. It was found that the uppermost hydrophobic layer that forms on removal of the cartilage from synovial fluid was made up mostly of phospholipid.…”
Section: Boundary Lubricating Components Of Synovial Fluidmentioning
confidence: 99%
“…An articular cartilage surface is covered by a cell-free lamina splendens (LS) consisting mainly of the HA and phospholipids. 17 An important structural and metabolic unit of articular cartilage is a chondron. 11 It includes a chondrocyte and its pericellular matrix (PM) bordered with a pericellular capsule (PC).…”
Section: Cartilage As a Subject Of Regenerationmentioning
confidence: 99%